2022
DOI: 10.1111/phpp.12765
|View full text |Cite
|
Sign up to set email alerts
|

Will repeated Intense Pulsed Light (IPL) treatment sessions affect facial skin sensitivity? Results of a twelve‐Month, prospective, randomized split‐face study

Abstract: Sensitive skin is a frequent complaint among the general population, in patients, and among subjects suffering from itchiness. 1 The occurrence of unpleasant sensations (stinging, burning, pain, pruritus, and tingling) in response to stimuli that cannot be explained by lesions attributable to any skin disease is defined as sensitive skin syndrome. 2 As sensitive skin syndrome is a self-diagnosed condition lacking clinical or histologic evaluations, little is known about its underlying pathophysiology. Large ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…Studies have confirmed that IPL is effective in the control of erythema and telangiectasia in the treatment of rosacea, acne, and traumatic scarring 17–19 . However, IPL could aggravate skin barrier dysfunction when it was given to patients within inappropriate time 12,20 . In this study, we demonstrated that the erythema area was reduced, and further effects could be achieved after combining IPL with SWRF.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Studies have confirmed that IPL is effective in the control of erythema and telangiectasia in the treatment of rosacea, acne, and traumatic scarring 17–19 . However, IPL could aggravate skin barrier dysfunction when it was given to patients within inappropriate time 12,20 . In this study, we demonstrated that the erythema area was reduced, and further effects could be achieved after combining IPL with SWRF.…”
Section: Discussionsupporting
confidence: 52%
“…[17][18][19] However, IPL could aggravate skin barrier dysfunction when it was given to patients within inappropriate time. 12,20 In this study, we demonstrated that the erythema area was reduced, and further effects could be achieved after and exaggerated immersion tests, to the evaluation of itching and quantitative sensory testing. 2 However, there is still a lack of international consensus on the preferred method so that sensory tests were not taken in this study.…”
Section: Ta B L E 1 Characteristics Of the Patients With Sensitive Skinmentioning
confidence: 56%
“…UV (100-400nm) can cause skin sunburn, in ammation, aging, and cancer [6,7]. Intense pulsed light (IPL) has been con rmed with anti-aging effects in clinical practice, whereas the mechanism is unclear [8,9].…”
Section: Introductionmentioning
confidence: 99%